New injectable scaffolds for cell and drug delivery - Hamilton, Lloyd George (2009)
An injectable scaffold system for the delivery of cells and growth factors was developed in this project to enhance healing of bone fractures. The project was focused to meet the clinical need for an off-the-shelf synthetic biodegradable bone graft material. The concept required the injection of a paste to fill defects then rapidly solidify to a mechanically supportive macroporous structure. The injectable paste was developed from a two-component biodegradable microparticle scaffold based on poly(lactic-co-glycolic acid) (PLGA) and comprised of a versatile temperature insensitive (type 1) carrier and an adhesive (type 2) component made temperature sensitive with the addition of poly(ethylene glycol) (PEG) as a plasticizer. The plasticized adhesive type 2 component achieved wet compressive strengths up to 18 MPa at 37 °C after 24 hours. The sintering strategy utilised the changes in viscoelastic and mechanical properties that occur in the glass transition region of amorphous polymers. The specific mechanism devised in this thesis exploited the biocompatibility and diffusivity of PEG to increase polymer glass transition temperature in the wet sintering process.